2009
DOI: 10.1111/j.1939-1676.2008.0238.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione, Cysteine, and Ascorbate Concentrations in Clinically Ill Dogs and Cats

Abstract: Background: Oxidative stress plays a role in the pathogenesis of many systemic diseases. Hospitalized human patients are glutathione, cysteine, and ascorbate deficient, and antioxidant depletion has been correlated with poor clinical outcome. To date little is known about antioxidant concentrations in hospitalized veterinary patients. The purpose of this study was to determine whether ascorbate, cysteine, or glutathione depletion is present in ill dogs and cats compared with healthy controls.Hypothesis: Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 50 publications
2
57
3
6
Order By: Relevance
“…Another study reported that GSH in cats, dogs, and humans were 1.97 ± 0.07, 1.98 ± 0.15, and 2.26 ± 0.09 mmol/L RBC, respectively (Harvey and Kaneko 1976). The study in clinically ill dogs also showed a decrease in erythrocyte glutathione concentration (Viviano et al 2009). …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Another study reported that GSH in cats, dogs, and humans were 1.97 ± 0.07, 1.98 ± 0.15, and 2.26 ± 0.09 mmol/L RBC, respectively (Harvey and Kaneko 1976). The study in clinically ill dogs also showed a decrease in erythrocyte glutathione concentration (Viviano et al 2009). …”
Section: Discussionmentioning
confidence: 92%
“…There was no association between age and oxidative stress parameters in the present study. In a study of clinically ill cats, there was no significant correlation between age and oxidative stress parameters (GSH, cysteine, and ascorbate concentration) (Viviano et al 2009). The most common breeds of CKD cats included domestic short hair and Siamese breed cats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For feline immunodeficiency virus-infected cells supplementation of Vitamin C resulted in an inhibition of apoptosis and virus replication [35]. Furthermore, the determination of ill cats showed a high ascorbate concentration in plasma which function as a potential species response to oxidative stress [36]. Our results, however, suggested the detrimental effect of Vitamin C supplementation on cat follicle survival (Figure 2) in the ovarian cortex.…”
Section: Discussionmentioning
confidence: 74%